Field evaluation of different biopesticides for Aphid Pest Management in Wheat (Journal of Agriculture and Biology, 2025)
Wheat yield losses are caused by insect infestations. Aphids are important wheat pests that reduce economic production. Increasing wheat yields requires aphid management. Cherry oat aphid, Rhopalosiphum padi Linnaeus, green bug, Schizaphis graminum Rondani, and corn leaf aphid, Rhopalosiphum maidis. Fitch have all been known to damage wheat crops. Pests are controlled only by insecticides. Increased synthetic insecticide use has led to pest resistance and reappearance. Alternatively, botanicals and pesticides can alter aphid activity. The current research considers the importance of aphid management. Neem, Azadirachta indica A. Juss, Kortuma, Citrullus colocynthis Linnaeus, Tobacco, Nicotiana tabacum Linneaus, silver nanoparticle spray, S1 bacteria, Bacillus wiedmanni (S1B), Biopesticide (Bio-N), one insecticide Advantage, and Control were tested against wheat aphid and their biological control, ladybird beetles. Field wheat trials were conducted at MNS University of Agriculture, Multan. Randomised whole block design under factorial was replicated three times. Before and after 24, 48, 72, and 168 hours were recorded. Aphid population dynamics showed substantial variations between kortuma, Ag nanoparticle, and Bio-N treatments. Significant ladybird beetle/plant populations were seen in kortuma and silver nanoparticle treatments during the second week of spraying (p < 0.05). Due to less resistance, biopesticides such Ag nanoparticle, Bio-N, S1B, and kortuma performed better than all other treatments. Aphid populations were higher in the control and biopesticide treatments like neem and tobacco after certain hours. We found that biopesticides worked better than conventional treatments due to lower resistance and natural production.